Assessing the Economic Resilience of the Poor and Vulnerable Groups East Java Province in the Middle of the Covid-19 Pandemic : Susenas Data Study 2019 - Herman Palani; Ahmad Zufar Robbani (East Java Economic Journal, 2020)
The COVID-19 pandemic has had a significant economic impact, especially on the poor and vulnerable groups in East Java, which is one of the provinces most affected by this pandemic. However, studies that focus on assessing the level of economic resilience of the poor and vulnerable groups in East Java are still limited. This study was conducted to analyze the economic resilience of the poor and vulnerable groups in East Java in terms of various characteristics such as access to social safety nets, asset ownership, savings account ownership, employment sector, and access to public facilities. Using Susenas data as the main data source and quantitative descriptive analysis method, this study shows that the poor and vulnerable groups have low resilience, limited access to social safety nets and low self-defense systems are two important factors that affect resilience levels.It will be used to evaluate existing policies and provide recommendations for future policy improvements.